De minimis aid in agriculture and its registration in Spain. The new legislative project for the organisation of agricultural information - Muñiz Espada, Esther (Przegląd Prawa Rolnego, 2022)
This article analyses the register and rules on the basis of which de minimis aid is granted in Spain. The characteristics and main types of agricultural activities that are subject to registration are characterised. The undertaking of this study was prompted by the peculiarity of administrative registers in Spain, which, by virtue of defining the rules of agricultural activity, belong to agricultural law, while these rules call for an urgent reform in order to increase their efficiency.